A data analysis method for identifying deterministic components of stable and unstable time-delayed systems with colored noise - K. Patanarapeelert (2018)
A method is proposed to identify deterministic components of stable and unstable time-delayed systems subjected to noise sources with finite correlation times (colored noise). Both neutral and retarded delay systems are considered. For vanishing correlation times it is shown how to determine their noise amplitudes by minimizing appropriately defined Kullback measures. The method is illustrated by applying it to simulated data from stochastic time-delayed systems representing delay-induced bifurcations, postural sway and ship rolling. © 2006 Elsevier B.V. All rights reserved.